Dashboard de seguimiento integral al estado de salud de los datos de una organización - Rodríguez Zabala, Constanza; Moreno Arias, Nelson I. (Universidad Antonio Nariño, 2022)
Data Quality within Organizations is one of the most important issues to manage, since without high quality data the different layers of the organization are affected at a strategic, tactical and operational level, this is reflected in poor management of clients, reprocesses, cost overruns, deterioration of the corporate image. In this document we want to present how, through the application of good practices, organizations can carry out a comprehensive monitoring of the state of health of the data, this is how what has been described in the Data Management Fundamentals Guide has been taken into account. of the Data Management Association DAMA in its version 2 specifically in the data quality chapter, where it indicates that for the continuous improvement of data quality it is key that organizations consider the Deming iterative cycle that means "Plan, Do, Do". Check and Act”.